Competition policy issue in drug companies : a management accountant's view / Tengku Akbar Tengku Abdullah - Tengku Abdullah, Tengku Akbar (Faculty of Accountancy, 2003)
International Journal of the Economics of Business produced a special issue on 'Symposium on the US brand name prescription drug antitrust legislation' in 1997. This case involved fascinating scientific and policy issues including price discrimination. Economic scholars contributed to the debate. This paper gives a management accountant's view on the competition policy issue. It clarifies the competition policy issue using diagnostic tools (an analytical construct and concepts of cost). These diagnostic tools have been able to give insights into the issue.